2019
DOI: 10.3390/nu11092210
|View full text |Cite
|
Sign up to set email alerts
|

Oral Tolerance Induction to Newly Introduced Allergen is Favored by a Transforming Growth Factor-β-Enriched Formula

Abstract: Food allergies have become a major healthcare concern, hence preventive efforts to ensure oral tolerance induction to newly introduced antigens are particularly relevant. Given that transforming growth factor-β (TGF-β) plays a key role in immune tolerance, we tested whether an infant formula enriched with TGF-β would improve oral tolerance induction. A partially hydrolyzed whey protein-based formula was enriched with cow's-milk-derived TGF-β (TGF-β-enriched formula) by adding a specific whey protein isolate (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 49 publications
4
15
0
Order By: Relevance
“…The clinical relevance of the finding that micellar casein and whey powder, independent of the manufacturer, strongly increase TGF-β target genes and decrease ID1 and ID3 genes, remains unclear but leaves room for speculations. Considering that milk TGF-β can reduce the allergic reactions in ovalbumin-tolerized mice [ 3 ] and ameliorate tissue damage in colitis and endotoxemia murine models [ 4 ], some beneficial effects of the TGF-β in micellar casein and whey powder can also be assumed. Particularly in athletes, micellar casein and whey powder support muscle growth upon weight training [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The clinical relevance of the finding that micellar casein and whey powder, independent of the manufacturer, strongly increase TGF-β target genes and decrease ID1 and ID3 genes, remains unclear but leaves room for speculations. Considering that milk TGF-β can reduce the allergic reactions in ovalbumin-tolerized mice [ 3 ] and ameliorate tissue damage in colitis and endotoxemia murine models [ 4 ], some beneficial effects of the TGF-β in micellar casein and whey powder can also be assumed. Particularly in athletes, micellar casein and whey powder support muscle growth upon weight training [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Milk should not be restricted to its nutritional aspects being a rich source of the TGF-β [ 2 ]. Milk TGF-β is supposed to exert at least part of the beneficial activity of milk in vivo, for example to reduce the allergic reactions in ovalbumin-tolerized mice [ 3 ] and to ameliorate tissue damage and mortality in colitis and endotoxemia murine models [ 4 ]. In vitro, TGF-β activity is identified by its ability to regulate target genes, most notably interleukin11 (IL11), NADPH oxidase 4 (NOX4) and proteoglycan4 (PRG4) based on independent screening approaches [ 5 , 6 , 7 ], and some of TGF-β effects in vivo are mediated via IL11 [ 8 , 9 ] and NOX4 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When fed a TGF-β-enriched formula to mice with ovalbumin (OVA)-induced FA, allergenic responses were decreased when compared with the control group. IgE, IgG1, mMCP-1, and correlated cytokine levels all indicated decreased allergic responses [68]. Carrier et al [69] found that Th3 cells can act directly and induce Foxp3 + to act indirectly as the central mediator of peripheral immune tolerance using a transgenic mouse model of TGF-mice.…”
Section: T Cell and Oral Tolerancementioning
confidence: 99%